2007
DOI: 10.2165/00044011-200727040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Esmolol, Lidocaine and Fentanyl on Haemodynamic Responses to Endotracheal Intubation

Abstract: It can be concluded that administration of esmolol 1.5 mg/kg 2 minutes before intubation prevents tachycardia and an increase in RPP caused by laryngoscopy and tracheal intubation, and can be beneficial when administered before laryngoscopy and tracheal intubation in patients with tachycardia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 26 publications
4
35
0
7
Order By: Relevance
“…In the current study, we determined that esmolol was the most effi cient agent to depress the refl ex response to laryngoscopy and tracheal intubation, in parallel with previous studies 27,32,33 . Prolonged QT interval may cause arrhythmias such as polymorphic ventricular tachycardia or ventricular fi brilation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In the current study, we determined that esmolol was the most effi cient agent to depress the refl ex response to laryngoscopy and tracheal intubation, in parallel with previous studies 27,32,33 . Prolonged QT interval may cause arrhythmias such as polymorphic ventricular tachycardia or ventricular fi brilation.…”
Section: Discussionmentioning
confidence: 57%
“…However, literature on this matter is confounding. Other studies demonstrated that lidocaine administration before intubation was unable to suppress the laryngoscopy and intubation-related sympathetic activity 27,32,33,38 . In addition, signifi cant MAP increases were observed in lidocaine groups after intubation in Owczuk et al's 17 study, which raises the possibility of insuffi cient lidocaine effi cacy in inhibiting sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5] Fentanyl is a short acting synthetic opioids agonist 75-125 times more potent than morphine. Several trials have tried varying doses from 2µg/Kg-8 µg/Kg given 1 minute to 10 minutes before intubation.…”
Section: A Comparative Evaluation Of Dexmedetomidine and Fentanyl To mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Thus different drugs such as local anesthetics, opioids, calcium channel blockers, short acting β-adrenergic blockers, and their combinations have been used to prevent this hemodynamic responses but none was found to be most effective. [8][9][10][11][12][13][14] Fentanyl, a commonly used opioid along with hypnotic agents have been used to diminish hemodynamic responses to tracheal intubation. [15][16][17] Furthermore, lidocaine has a suppressive effect on the circulatory responses in patients undergoing laryngoscopy and tracheal intubation.…”
Section: Introductionmentioning
confidence: 99%